Evaluation of a “one-stop shop” for integrated harm reduction and primary care for people who inject drugs - Nadeen Ibrahim; Shaifer Jones; Katherine Rich; Lisandra Alvarez; Carolina Price; Natalie Kil; Frederick L. Altice; Jaimie P. Meyer (PLoS ONE, 2025)
Background People who inject drugs (PWID) experience high risk for HIV and HCV infection, which can be mitigated by harm reduction strategies, including syringe service programs (SSP). Understanding individuals’ patterns of substance use and SSP utilization is important for optimizing harm reduction strategies and disease prevention for PWID. Methods We evaluated demographic characteristics and service utilization from the New Haven Syringe Services Program (NHSSP), a low-threshold service delivery site in New Haven, Connecticut that provides fully integrated harm reduction and primary healthcare services to PWID. Site-specific data were extracted from the e2ctprevention database, managed by the Connecticut Department of Public Health, and EvaluationWeb from January 2017 to October 2023. We conducted a descriptive analysis of basic demographic and social characteristics of SSP clients, transaction characteristics, and service utilization. Statistical analyses were conducted using STATA v 16.1 and IBM SPSS Statistics (v 29.0.2.0). Results Among 1,189 unique individuals utilizing SSP during the observation period, most (65.2%) identified as men and white (73.3%), consistent with SSP clients regionally and nationally. The mean age of clients was 41 years (SD = 9.8); approximately half of participants were unstably housed and 80% were unemployed at intake. From June 2020 to October 2023, there were 7,238 transactions, which increased throughout the COVID-19 pandemic period. During this period, the program dispensed 1,860,621 syringes, in addition to other materials, including overdose education and naloxone distribution (OEND), and provided patient education on safer injecting techniques and wound care. Conclusion In this first comprehensive analysis of a large SSP since its inception and through the COVID-19 pandemic, we described important client characteristics and utilization of an array of syringe services from an integrated SSP. Findings suggest the SSP attracts a high volume of clients, provides on-demand services, and reaches a wide range of clients. Future research is needed to evaluate the impact of the program’s home-delivery service and increased outreach efforts. Despite limitations, the program’s success demonstrates the SSP can serve as a model for other harm reduction programs nationally.